PV Charging and Storage for Electric Vehicles - Bauer, Pavol; Chandra Mouli, Gautham Ram (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Electric vehicles are only 'green' as long as the source of electricity is 'green' as well. At the same time, renewable power production suffers from diurnal and seasonal variations, creating the need for energy storage technology. Moreover, overloading and voltage problems are expected in the distributed network due to the high penetration of distributed generation and increased power demand from the charging of electric vehicles. The energy and mobility transition hence calls for novel technological innovations in the field of sustainable electric mobility powered from renewable energy. This Special Issue focuses on recent advances in technology for PV charging and storage for electric vehicles.